Contribution of quantum chromodynamics condensates to the operator product expansion of Green functions of chiral currents. Issue 1 (28th March 2019) - Kadavý, T.; Kampf, K.; Novotný, J.
Abstract : In this paper, the basic properties of quantum chromodynamics (QCD) condensates are presented, together with theirs relation to the operator product expansion (OPE) and the two‐point and three‐point Green functions constructed of chiral currents. Next, our newest results for the contribution of the QCD condensates with dimension D  < 6 to the Green functions calculated within the framework of χ PT/R χ T, i.e. chiral perturbation theory or resonance chiral theory, are discussed. This matching of the OPE and such effective theories can lead to some constraints on the coupling constants, thus allowing us to obtain some unknown parameters of the chiral/resonance Lagrangian.